2019
DOI: 10.1039/c9sc03324f
|View full text |Cite
|
Sign up to set email alerts
|

Silicon clusters with six and seven unsubstituted vertices via a two-step reaction from elemental silicon

Abstract: A synthetic shortcut to molecules that contain several unprotected silicon atoms comprising the whole range from localized to delocalized Si–Si bonds.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
30
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 26 publications
(33 citation statements)
references
References 77 publications
2
30
0
1
Order By: Relevance
“…It is known that the deltahedral clusters possess very characteristic Raman spectra , . We recently showed that endohedrally filled clusters show in contrast to the empty clusters a shift of the characteristic Raman lines of the empty clusters but also additional signals at higher wave numbers .…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…It is known that the deltahedral clusters possess very characteristic Raman spectra , . We recently showed that endohedrally filled clusters show in contrast to the empty clusters a shift of the characteristic Raman lines of the empty clusters but also additional signals at higher wave numbers .…”
Section: Resultsmentioning
confidence: 95%
“…It is known that the deltahedral clusters possess very characteristic Raman spectra. [20,[47][48][49][50] We recently showed that endohedrally filled clusters show in contrast to the empty clusters a shift of the characteristic Raman lines of the empty clusters but also additional signals at higher wave numbers. [51] We found that Raman spectroscopy can also be applied for the Sn containing phases to show if filled clusters are present, in contrast to powder X-ray diffraction experiments that show too many reflections to determine changes in the cell parameters.…”
Section: Raman Spectroscopymentioning
confidence: 99%
“…Most of the synthetically accessible molecular silicon cages, such as Fässler’s [R 2 Si 9 ] 2– anions, Kyushin’s decasilahexa­hydrotriquinacene, Marschner’s decasilaadamantane, Scheschkewitz’s siliconoids, or the above-mentioned silatetrahedranes and -cubanes present chemically rather innocent (bulky) organyl groups to their environments. Hydrogenated species are rare, and functionalized derivatives feature mainly low-valent, nucleophilic Si sites .…”
mentioning
confidence: 99%
“…Thus, by treatment of solid K 4 Ge 9 with stoichiometric amounts of an acetonitrile solution of chloro-tris(trimethylsilyl)silane the twoand three-fold silylated clusters [Ge 9 {Si(TMS) 3 } 2 ] 2À 24 and [Ge 9 {Si(TMS) 3 } 3 ] À 25 are obtained, respectively. The transfer of this method to elusive [Si 9 ] clusters in the phase K 12 Si 17 yielding [Si 9 {SiR 3 } 2 ] 2À , [Si 9 {SiR 3 } 3 ] À (R ¼ TMS, t Bu 2 H), 26,27 [Si 9 H 2 ] 2À , 28 and [Si 9 H] 3À 29,30 shows the huge potential of this synthetic protocol using polar intermetallic compounds (Zintl phases) as precursors.The addition of functional groups such as silyl fragments 24,31-35 to bare [Ge 9 ] allowed for a stabilization and…”
mentioning
confidence: 99%